Reason fulfilled by revelation: the 1930s Christian philosophy debates in France - Sadler, Gregory B. (The Catholic University of America Press, 2011)
A collection of articles and presentations from French journals and learned societies appearing from 1931 to 1936, translated into English with considerable supporting apparatus